Analisis Konseptual Rational Emotive Behavior Therapy (REBT) Untuk Penanganan Stres Akademik Mahasiswa - Debi Anggraeni; Fitri Husaibatul Khairat Hasibuan; Pebrisa Amrina (Social Science Academic, 2026)
Academic stress is almost always faced by students, both in Indonesia and globally, with impacts ranging from sleep pattern disruptions to decreased learning achievement. Rational emotive behavior therapy (REBT) is a widely used approach to deal with this condition, departing from the view that emotional disorders are not caused directly by events, but by individual beliefs in interpreting them. Comprehensive studies that link the basic concepts of REBT, the mechanism of ABCDE and empirical evidence  of irrational beliefs in students are still rare. This study analyzes the concept of REBT in explaining the formation of academic stress, identifies development opportunities and the relevance of its application in higher education and examines its intervention mechanisms. The research uses conceptual analysis with a literature method. The literature is searched from reputable scientific databases such as Google scholar, Frontiers, Elsevier etc. with the keywords Rational Emotive Behavior Therapy and academic stress. The synthesis shows that the main source of academic stress itself, but also in students' irrational beliefs in the form of demandingness, awfulizing, low frustration tolerance, and self downing. The disputing process in the ABCDE method is a key mechanism for transforming beliefs into rational and adaptive, with stronger effectiveness when applied systematically by trained practitioners. REBT has great potential as a counseling guidance service in Indonesian universities to overcome academic stress from its cognitive roots, although empirical verification in Indonesian students is still needed.